2018
DOI: 10.1186/s13567-018-0583-1
|View full text |Cite
|
Sign up to set email alerts
|

The CO2-dependence of Brucella ovis and Brucella abortus biovars is caused by defective carbonic anhydrases

Abstract: Brucella bacteria cause brucellosis, a major zoonosis whose control requires efficient diagnosis and vaccines. Identification of classical Brucella spp. has traditionally relied on phenotypic characterization, including surface antigens and 5–10% CO2 necessity for growth (CO2-dependence), a trait of Brucella ovis and most Brucella abortus biovars 1–4 strains. Although molecular tests are replacing phenotypic methods, CO2-dependence remains of interest as it conditions isolation and propagation and reflects Bru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
24
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 62 publications
9
24
2
2
Order By: Relevance
“…We report a forward genetic selection strategy to identify B. ovis mutants that grow spontaneously under standard atmospheric conditions, and have defined the genetic changes in these strains by whole genome sequencing. In agreement with recent results from Perez-Etayo and colleagues (27), we found that B. ovis mutants selected to grow in a standard atmosphere carry a frameshift mutation at the 3' end of a b-carbonic anhydrase gene, bcaABOV. Carbonic anhydrases catalyze the reversible hydration of CO2 to bicarbonate, an essential metabolic building block (28), and plasmidbased expression of the frameshifted bcaABOV allele or of functional Escherichia coli carbonic anhydrases, can or cynT, are sufficient to enable growth of B. ovis in a standard atmosphere.…”
Section: A Model To Investigate Brucella Responses To Co2 Limitationsupporting
confidence: 93%
See 4 more Smart Citations
“…We report a forward genetic selection strategy to identify B. ovis mutants that grow spontaneously under standard atmospheric conditions, and have defined the genetic changes in these strains by whole genome sequencing. In agreement with recent results from Perez-Etayo and colleagues (27), we found that B. ovis mutants selected to grow in a standard atmosphere carry a frameshift mutation at the 3' end of a b-carbonic anhydrase gene, bcaABOV. Carbonic anhydrases catalyze the reversible hydration of CO2 to bicarbonate, an essential metabolic building block (28), and plasmidbased expression of the frameshifted bcaABOV allele or of functional Escherichia coli carbonic anhydrases, can or cynT, are sufficient to enable growth of B. ovis in a standard atmosphere.…”
Section: A Model To Investigate Brucella Responses To Co2 Limitationsupporting
confidence: 93%
“…Replacing bcaABOV with bcaABAB2308 enabled growth of B. ovis in 0.04% CO2 (Fig. 4C), consistent with Perez-Etayo et al (27). Replacing bcaABOV with the frameshifted bcaABAB pseudogene did not enable B. ovis growth in a standard atmosphere (Fig.…”
Section: Functional B Abortus Bcaa Alleles Are Rapidly Selected Fromsupporting
confidence: 88%
See 3 more Smart Citations